Reducción presupuestaria en el sector educación, la inseguridad de los planteles educativos - Zúñiga García, Yadira Mariuxi (2020)
This Professional Project Report is executed to determine the incidence of the budget reduction in the education sector and the insecurity in the educational establishments by eliminating the budgets for security and surveillance services, a situation that was exacerbated by the pandemic when activities were suspended The research work is carried out at the Juan E Verdesoto Amie 12H00096 Basic Education School of the 12D01C05 Circuit belonging to the District Directorate of Education 12D01 Babahoyo, Baba and Montalvo, as it is a large institution that is located in the central sector of the city of Babahoyo and which has a significant inventory of movable property, demonstrating the great problem of insecurity faced by urban educational establishments and those with the greatest distress in rural areas. . An interview was conducted with the Director of the Institution in order to know what his opinion is about the insecurity in the Educational Facilities, teachers and parents agree that the insecurity that institutions currently face is worrying. Thanks to the analysis of the results it is possible to determine what will be done? What is it going to be done for? After presenting the proposal and its results.